PENINGKATAN KETERAMPILAN PERANCANGAN DAN PEMBUATAN RAK SANDAL MINIMALIS ERGONOMIS BERBAHAN BESI NAKO BAGI SISWA SEKOLAH MENENGAH KEJURUAN NEGERI (SMKN) 7 TANGERANG BANTEN - I Wayan Sukania; Melynia Novita P; Elisha Elisha (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Slipper rack is a place to put sandals or shoes. The existence of this shelf is very important in the mosque in the SMKN 7 Tangerang environment. Slipper rack design that meets the ergonomics and aesthetic aspects is very important. From the side of SMKN 7 students, based on information from the academic section, it is known that the supply of product design theory and welding theory is felt to be lacking. Likewise, the practice of making welding products is not carried out in this school. Therefore, the design and manufacture of welding products is in great demand by students. Considering that students are beginners, the sandal rack products that are designed and made are functional, minimalist and ergonomic. The training activities were carried out in 2 stages, namely the first stage in the form of exposing theories and insights and the second stage in the form of field work practices to realize the sandal rack product. The first stage produces a variety of sandal rack concepts. Field practice in realizing the selected sandal rack design resulted in 3 product units. There are several job skills that are improved in this training, namely measuring materials, cutting, rolling. sanding, grinding, welding and painting. While the enhanced insight is marketing, ergonomics and product design. Based on the questionnaire data provided, there was an increase in participants' insight and understanding of the importance of market research by 36%, an increase in knowledge and understanding of the role of ergonomics in the design of a product used by humans by 42.9%, an increase in knowledge and understanding of the stages of designing and developing a commercial product. by 50%, increasing knowledge and understanding of how to use welding machines, grinding machines and supporting equipment in welding workshops by 92.9%, increasing experience working in teams/groups in making a product by 100%. A total of 98.2 participants stated that the instructor's guidance, materials and training methods were satisfactory.Rak sandal adalah tempat untuk meletakkan sandal atau sepatu. Keberadaan rak ini sangat penting di masjid dalam lingkungan SMKN 7 Tangerang. Desain rak sandal yang memenuhi aspek ergonomi dan estetika sangat penting. Dari sisi siswa SMKN 7, berdasarkan informasi dari bagian akademik diketahui bahwa pembekalan teori perancangan produk dan teori pengelasan dirasakan masih kurang. Demikian juga praktik pembuatan produk hasil pengelasan tidak dilakukan di sekolah ini. Oleh karena itu kegiatan pelatihan perancangan dan pembuatan produk hasil pengelasan sangat diminati oleh siswa. Mengingat para siswa sebagai pemula maka produk rak sandal yang rancang dan dibuat adalah yang fungsional, minimalis dan ergonomis. Kegiatan pelatihan dilakukan dalam 2 tahap yaitu tahap pertama berupa pemaparan teori serta wawasan dan tahap kedua berupa praktik kerja lapangan mewujudkan produk rak sandal. Tahap pertama menghasilkan berbagai konsep rak sandal. Praktik lapangan mewujudkan desain rak sandal terpilih menghasilkan 3 unit produk. Adapun beberapa keterampilan pekerjaan yang ditingkatkan pada pelatihan ini yaitu mengukur bahan, memotong, mengerol. mengampelas, menggerinda, mengelas dan mengecat. Sedangkan wawasan yang ditingkatkan yaitu pemasaran, ergonomi dan perancangan produk. Berdasarkan data kuisioner yang diberikan, terjadi peningkatan wawasan dan pemahaman peserta terhadap pentingnya riset pasar sebesar 36 %, peningkatan pengetahuan dan pemahaman peranan ergonomi dalam perancangan sebuah produk yang digunakan manusia sebesar 42,9%, peningkatan pengetahuan dan pemahaman tahapan perancangan dan pengembangan sebuah produk komersial sebesar 50%, peningkatan pengetahuan dan pemahaman cara menggunakan mesin las, gerinda mesin dan peralatan pendukung di bengkel pengelasan sebesar 92,9%, peningkatan pengalaman bekerja dalam team/kelompok dalam pembuatan sebuah produk sebesar 100%. Sebanyak 98,2 peserta menyatakan bahwa penduan instruktur, materi dan metode pelatihan memuaskan.